Incarceration, families, and communities: recent developments and enduring challenges - Wakefield, Sara (Crime and justice, 2022)
Mass incarceration has fundamental adverse effects that include weakening families and intimate relationships, altering children’s life chances, and undermining communities. Serious work on those effects began in the late 1990s and laid foundations on which subsequent research has built. More recent work, especially in the past dozen years, is more complex and has produced findings that are more nuanced and mixed. It is also theoretically and conceptually richer. The newer work involves substantially greater cross-disciplinary engagement, draws on new and more diverse data sources, and pays greater attention to pathways into prison. Fundamental challenges persist. They include measurement problems, overlap between the criminal justice and other governmental systems (e.g., education, public health, social welfare), and generalizability issues. Mixed results, definitional disagreements, and measurement challenges should encourage researchers to embrace complexity in the study of the effects of incarceration on family and community life.